2020
DOI: 10.1371/journal.pone.0223464
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular dynamic simulations to investigate the structural impact of known drug resistance mutations on HIV-1C Integrase-Dolutegravir binding

Abstract: Resistance associated mutations (RAMs) threaten the long-term success of combination antiretroviral therapy (cART) outcomes for HIV-1 treatment. HIV-1 Integrase (IN) strand transfer inhibitors (INSTIs) have proven to be a viable option for highly specific HIV-1 therapy. The INSTI, Dolutegravir is recommended by the World Health Organization for use as first-line cART. This study aims to understand how RAMs affect the stability of IN, as well as the binding of the drug Dolutegravir to the catalytic pocket of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…Our previous studies found low level of RAMSs against INSTIs (21). Our recent studies on CRF02_AG, reported that NOPs can have an effect on DTG binding with or without combination of primary mutation (19,24,28). In the current, study we analysed the CRF02_AG IN gene sequences for the presence of polymorphic and non-polymorphic mutations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous studies found low level of RAMSs against INSTIs (21). Our recent studies on CRF02_AG, reported that NOPs can have an effect on DTG binding with or without combination of primary mutation (19,24,28). In the current, study we analysed the CRF02_AG IN gene sequences for the presence of polymorphic and non-polymorphic mutations.…”
Section: Discussionmentioning
confidence: 95%
“…The IN mutations usually associated with reduced INSTIs susceptibility include both polymorphic mutations and non-polymorphic mutations (25,26). Other studies have reported that several NOPs can affect structural stability and exibility of the IN protein structure (27,28). Low rates of IN mutations against INSTIs were reported in Cameroon (21).…”
Section: Discussionmentioning
confidence: 99%
“…The IN mutations usually associated with reduced INSTIs susceptibility include both polymorphic mutations and non-polymorphic mutations [ 29 , 30 ]. Other studies have reported that several NOPs can affect structural stability and flexibility of the IN protein structure [ 31 , 32 ]. Previous researchers have reported low rates of IN mutations against INSTIs in Cameroon [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on CRF02_AG IN, we reported that accessory mutations can impact the binding of DTG with or without combination of primary resistance mutations [ 32 , 36 ]. In this study we analysed the CRF02_AG IN gene sequences for the presence of polymorphic and non-polymorphic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is, however, in agreement with a study by Chitongo et al, 2020 that showed that one known major resistance mutation, G140S, had an effect on DTG drug binding in HIV-1C IN in combination with NOP’s. Therefore, NOPs alone have a negligible effect on drug binding [ 53 ].…”
Section: Discussionmentioning
confidence: 99%